2012
DOI: 10.1007/s11434-012-5143-x
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-based ambipolar electronics for radio frequency applications

Abstract: Graphene is considered as a promising material to construct field-effect transistors (FETs) for high frequency electronic applications due to its unique structure and properties, mainly including extremely high carrier mobility and saturation velocity, the ultimate thinnest body and stability. Through continuously scaling down the gate length and optimizing the structure, the cut-off frequency of graphene FET (GFET) was rapidly increased and up to about 300 GHz, and further improvements are also expected. Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 92 publications
0
21
0
1
Order By: Relevance
“…Many excellent reviews have summarized the progress of graphene field-effect transistors (GFETs), including material synthesis, material characterization, device fabrication, and characterization, as well as various GFETbased applications [5][6][7][8][9]. One of the best properties of a GFET is its ambipolar characteristics, and it is best used in RF components [10][11][12][13]. To date, several GFET-based RF components have been demonstrated, such as oscillators [14][15][16][17][18][19][20], phase shifters [21,22], amplifiers [23][24][25][26], mixers [27][28][29][30][31], and frequency multipliers [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Many excellent reviews have summarized the progress of graphene field-effect transistors (GFETs), including material synthesis, material characterization, device fabrication, and characterization, as well as various GFETbased applications [5][6][7][8][9]. One of the best properties of a GFET is its ambipolar characteristics, and it is best used in RF components [10][11][12][13]. To date, several GFET-based RF components have been demonstrated, such as oscillators [14][15][16][17][18][19][20], phase shifters [21,22], amplifiers [23][24][25][26], mixers [27][28][29][30][31], and frequency multipliers [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, graphene has been considered an excellent candidate for the next generation of high-frequency electronics. [35][36][37][38][39][40][41] The back-gate graphene transistor, in which a SiO 2 layer and a doped silicon substrate usually act as back-gate dielectric and the back-gate, respectively, is being studied by many researchers and will ne very useful in graphene nanoelectronics. Novoselov et al demonstrated the unique properties of graphene with a back-gate graphene transistor.…”
Section: Transistor Devicesmentioning
confidence: 99%
“…33 To overcome the parasitic capacitance of back-gate graphene transistors, the top-gate graphene transistor with a high cut-off frequency (f T ) and the maximum oscillation frequency (f max ) is preferred to realize the promising application of graphene in RF electronics. 5,7,8,39 Lemme et al reported the first top-gate graphene transistor, representing an important milestone and starting the field of graphene radio frequency (RF) devices. 42 Various configurations of graphene transistors have been reported in the past several years and the properties of graphene transistors have been greatly improved.…”
Section: Transistor Devicesmentioning
confidence: 99%
“…[1][2][3][4][5][6] The good conductivity along with the low thickness allows for its application as transparent electrodes. 7 Field-effect transistors based on 2-dimensional materials have already been realized.…”
Section: Introductionmentioning
confidence: 99%